Manajemen Pendidikan Islam dalam Pengembangan Madrasah - Muazin Hamdi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The emergence of high-quality Islamic educational institutions in Indonesia is a result of Islamic modernization that integrates meritocracy principles with traditional educational values. This study aims to analyze the process of school or madrasah development in improving educational quality and management through strategic steps such as needs analysis, planning, implementation, and evaluation. The method used is a literature review to evaluate knowledge and findings from various sources. The results indicate that the development of schools or madrasahs includes enhancing curricula, facilities, teacher welfare, management, and community participation. This process is also relevant in addressing the challenges of globalization, technology, and 21st-century skills requirements. The implications suggest that continuous and adaptive development is necessary to create effective learning environments and ensure educational institutions are prepared for a competitive future.